Experimental investigation of the effects of cathode position on HK40 hall effect thruster performance and cathode coupling - Turan, Nazlı. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
Electric propulsion systems are being developed for orbital and deep space maneuvers of spacecraft. Hall e ect thrusters, studied under electric propulsion systems, are among the most preferred thrusters for future space missions. Hall e ect thrusters utilize electric and magnetic elds. The propellant gas, such as Argon or Xenon, is ionized by the cathode electrons which are trapped by the magnetic eld lines and the positive ions are accelerated out of the thruster by Lorentz force. HK40 Hall e ect thruster, which is designed and manufactured at BUSTLab, is used in this study. Magnetic eld measurements and the magnetic modeling of the HK40 Hall e ect thruster are conducted. Initial characterization tests of BUSTLab hollow cathode are carried out and the thermal model of the cathode is completed. In Hall thrusters, external magnetic eld forms a pattern called separatrix. In this study, the e ects of the position of hollow cathode with respect to separatrix surfaces are investigated by moving the cathode using a 2D translational stage. The e ects of magnetic eld topology and the cathode location on ionization e ciency and thrust are studied. Additionally, two di erent electrical wiring con gurations for the thruster-cathode system are studied, and the e ects of the vacuum tank on the cathode and the thruster operation are investigated.
Keywords: Cathode ray oscillographs.; Hall effect devices.